Sarcoidosis in north African people: about 35 cases - Gargouri, Rahma; Fenina, Wafa; Al Juaidi, Mohamed; Feki, Walid; Fendri, Hela; Msaed, Sameh; Moussa, Nedia; Mnif, Zeineb; Kammoun, Samy (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Sarcoidosis is a systemic disease of unknown cause characterized by the formation of non-caseating granulomatous inflammation in various organs, mainly  lungs and intrathoracic lymph nodes. Its clinical and paraclinical presentation can vary from mild to life-threatening. Our objective is to study the clinical, paraclinical and evolution profile of mediastino-pulmonary sarcoidosis.Methods: This is a retrospective, descriptive and analytic study conducted over a 20-year period (January 2002 to December 2022). It compiled records of patients who were followed up for confirmed mediastino-pulmonary sarcoidosis.Results:  The study included 35 patients with a mean age of 56.69 ± 14.42 . There was a clear predominance of female patients, with a male-to-female sex ratio of 0.346. The most common functional respiratory signs were dyspnea (82.9%) and dry cough (80%). Extra-respiratory symptoms were noted in 45.7% of cases, with the most common being polyarthralgia (28.6%), xerophthalmia (20%) and xerostomia (14.3%). The most common parenchymal lesions were micronodules (71.4%), nodules (51.4%), and peribronchovascular thickening (40%). The The right upper lobe   (77.1%) and middle lobe (74.3%) were the most affected lobes. Hilar adenopathy (71.4%), paratracheal adenopathy (60%), and the aorto-pulmonary window (54.3%) were the most frequent lymph node involvements. Respiratory function tests revealed a restrictive ventilatory defect in 32% of cases and an obstructive ventilatory defect in 13% .Oral corticosteroids were initially administered in 60% of cases. Chronic respiratory failure was observed in 20% of cases. Factors significantly associated with an unfavorable outcome included hemoptysis (p=0.008), the need for corticosteroid treatment (p=0.009), Acute respiratory failure (p=0.05), and echographic dilation of the right cavities (p=0.002).Conclusions: The clinical phenotype of sarcoidosis can be extremely diverse.Thoracic computed tomography plays an important role in the diagnosis and monitoring of the disease. The evolution of sarcoidosis is variable and depends on the occurrence of complications.